Edukasi Diabetes Melitus Dan Pemeriksaan Gula Darah SewaktuDi Kelurahan Gantarang Keke Kabupaten Bantaeng - Nur Qadri Rasyid; Muawanah Muawanah; Wa Ode Rustiah; Effendy Rasiyanto (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2020)
Abstract Diabetes mellitus is a multifactorial disease that requires long-term care because it involves major changes in the physical and psychosocial dimensions of each patient. Early public education about diabetes mellitus is an important element to avoid complications of this disease. In addition, the community has never carried out early detection and screening of blood sugar. This community service is aimed at implementing a community-based education program that facilitates the community in increasing knowledge about early detection and self-care for Diabetes Mellitus in Gantarang Keke Village, Bantaeng Regency. The method of implementing community service consists of two stages, namely: 1) the preparation phase includes health counseling with a lecture method to the Gantarang Keke Village community 2) the implementation phase includes the implementation of an implementation program in the form of blood sugar screening. The results show that with the education carried out through counseling about diabetes mellitus, the Gantarang Keke Village community began to understand about Diabetes Militus, its causes, and management through lifestyle changes and can carry out healthy lifestyles, eating patterns / life style that can be done alone at home simply to be implemented as one of the prevention and maintain blood sugar levels. Most of the Kelurahan people who check blood sugar have the risk of developing Diabetes Mellitus. Keyword : Diabetes mellitus, Blood Sugar, Counseling